Efeito crônico do treinamento de força associado à restrição de fluxo sanguíneo no perfil de lipodistrofia e na qualidade de vida em sujeitos com HIV/AIDS - Oliveira, Janyeliton Alencar de (2020)
Introduction: Acquired Immunodeficiency Syndrome (AIDS) is an advanced clinical manifestation resulting from infection caused by the human immunodeficiency virus (HIV). One of the main adverse reactions to pharmacological treatment is the lipodystrophy syndrome (LS), which consists of the redistribution of subcutaneous fat. The main non-pharmacological tool is physical exercise and as an alternative proposal for this condition, there is the idea of exercise associated with the Blood Flow Restriction (BFR) technique, which allows effects similar to traditional strength training, but with low mechanical stress, improving aspects related to muscle strenght, SL and quality of life (QoL). Objective: To analyze the chronic effects of strength training with BFR on the profile of LS and on the QoL of people living with HIV / AIDS (PLWHA). Methodology: Eighteen subjects participated, aged between 18 and 61 years old, living with HIV / AIDS distributed in 3 groups: 1) strength training group + blood flow restriction (ST+BFRg): performed 4 strength exercises (flexion and extension of elbows and knees), associated with 50% BFR, at 30% of 1 RM; 2) Strength training (STg): performed the same exercises with 80% of 1 RM and; 3) Blood Flow Restriction group (BFRg): subjected to 50% BFR, with 4 cycles of 5 minutes of restriction and 5 minutes of reperfusion. The intervention lasted 12 weeks, with 36 sessions. Body composition, muscle strength and quality of life were assessed before and after 6 and 12 weeks. The data were analyzed in the software SPSS, 20.0, using Generalized Estimated Equations (GEE) with a gamma log, post hoc Bonferroni function and considering P≤0.05. Results: There was an increase in strength levels in the groups (TF and RFS) in 6 weeks and was accentuated with 12 weeks of training in the dominant and non-dominant limbs, in 4 movements analyzed: elbow flexion (W(4)=10.18; P=0.038), elbow extension (W(2)=9.23; P=0.003); knee flexion (W(4)=9.75; P=0.001); and knee extension (W(2)=9.75; P=0.001). As for body composition, segmented, an increase in muscle mass was observed in the right lower limb (MID) (W(2)=5.39; P<0.002) and left lower limb (LEM) (W(2)=8.84; P<0.003) and decreased fat mass of the right upper limb (MGMSD) (W(2)=8.84; P=0.001). The Hospital Anxiety and Depression Scale (HAD) showed a significant decline (W(2)=4.49; P<0.002) and QoL improved in 2 domains: environment (W(2)=6.55; P<0.003 ) and self-assessment (W(1) = 28.58; P<0.001) domains. Conclusion: Both low-load TF, associated with RFS, and, only RFS, reduced the effects of SL and improved QOL in PLWHA.